The Implementasi Supervisi dan Evaluasi Pendidikan (Studi Kasus di SMAN 1 Rupat) - Anju Nofarof Hasudungan (Program Studi Pendidikan Sejarah Universitas Riau, 2022)
Covid-19 pandemic that hit Indonesia had an impact on the education sector, including the implementation of supervision in schools. Therefore, strategies and techniques for carrying out supervision are needed in the midst of the Covid-19 pandemic. The purpose of this study is to describe the results of observations regarding the implementation of supervision at SMAN 1 Rupat in 2021 during the Covid-19 pandemic. The research method was carried out using a qualitative research type with a case study approach. Data collection is done by observation, documents, interviews, and literature study. The results showed that the implementation of educational supervision at SMAN 1 Rupat went well by utilizing platforms such as Google Meet and Whatsapp to support the implementation of educational supervision. This is inseparable from the strategies and techniques used in supervision. It is hoped that this can also be a best practice for other schools. However, there are still challenges, such as a poor internet network.